2/3 x + 1/4 x= -22/27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a; \(\dfrac{93}{17}\): \(x\) + (- \(\dfrac{21}{17}\)) : \(x\) + \(\dfrac{22}{7}\): \(\dfrac{22}{3}\) = \(\dfrac{5}{14}\)
\(\dfrac{94}{17}\) \(\times\) \(\dfrac{1}{x}\) - \(\dfrac{21}{17}\) \(\times\) \(\dfrac{1}{x}\) + \(\dfrac{3}{7}\) = \(\dfrac{5}{14}\)
\(\dfrac{72}{17}\) \(\times\) \(\dfrac{1}{x}\) + \(\dfrac{3}{7}\) = \(\dfrac{5}{14}\)
\(\dfrac{72}{17x}\) = \(\dfrac{5}{14}\) - \(\dfrac{3}{7}\)
\(\dfrac{72}{17x}\) = - \(\dfrac{1}{14}\)
17\(x\) = 72.(-14)
17\(x\) = - 1008
\(x\) = - 1008 : 17
\(x\) = - \(\dfrac{1008}{17}\)
Vậy \(x\) \(=-\dfrac{1008}{17}\)
b; - \(\dfrac{32}{27}\) - (3\(x\) - \(\dfrac{7}{9}\))3 = - \(\dfrac{24}{27}\)
- \(\dfrac{32}{27}\) + \(\dfrac{24}{27}\) = (3\(x\) - \(\dfrac{7}{9}\))3
(3\(x-\dfrac{7}{9}\))3 = - \(\dfrac{8}{27}\)
(3\(x-\dfrac{7}{9}\))3 = (- \(\dfrac{2}{3}\))3
3\(x-\dfrac{7}{9}\) = - \(\dfrac{2}{3}\)
3\(x\) = - \(\dfrac{2}{3}\) + \(\dfrac{7}{9}\)
3\(x\) = \(\dfrac{1}{9}\)
\(x\) = \(\dfrac{1}{9}\) : 3
\(x\) = \(\dfrac{1}{27}\)
Vậy \(x=\dfrac{1}{27}\)
Đề : Tìm x???
\(\frac{2}{3}x+\frac{1}{4}x=\frac{-22}{27}\)
\(x\left(\frac{2}{3}+\frac{1}{4}\right)=\frac{-22}{27}\)
\(x\left(\frac{8}{12}+\frac{3}{12}\right)=\frac{-22}{27}\)
\(x.\frac{11}{12}=\frac{-22}{27}\)
\(x=\frac{-22}{27}\div\frac{11}{12}\)
\(x=\frac{-22}{27}.\frac{12}{11}\)
\(x=\frac{-8}{9}\)
Vậy \(x=-\frac{8}{9}\).
1).( 27,56 x 35 ) + ( 27,56 x 67 ) - ( 27,56 x 2)
= (964 + 1846,52) - 55,12
=2810,52 - 55,12
= 2755,4
2).( 4x 35 ) x ( 25 x 5 ) x 2
= ( 140 x 125 ) x2
= 17500 x 2
=35000
4). 3/10
5). 1188
6). 61/6
\(1,=-\left(y^2+12y+36\right)=-y^2-12y-36\)
\(2,=-\left(16-8y+y^2\right)=-16+8y-y^2\)
\(3,=-\left(\dfrac{4}{9}+\dfrac{4}{3}x+x^2\right)=-\dfrac{4}{9}-\dfrac{4}{3}x-x^2\)
\(4,=-\left(x^2-3x+\dfrac{9}{4}\right)=-x^2+3x-\dfrac{9}{4}\)
\(5,-\left(2+3y\right)^2=-\left(4+12y+9y^2\right)=-4-12y-9y^2\)
.... mấy ý còn lại bn tự lm nhé, tương tự thhooi
1) \(-\left(y+6\right)^2=-y^2-12y-36\)
2) \(-\left(4-y\right)^2=-y^2+8y-16\)
3) \(-\left(x+\dfrac{2}{3}\right)^2=-x^2-\dfrac{4}{3}x-\dfrac{4}{9}\)
4) \(-\left(x-\dfrac{3}{2}\right)^2=-x^2+3x-\dfrac{9}{4}\)
5) \(-\left(3y+2\right)^2=-9y^2-12y-4\)
6) \(-\left(2y-3\right)^2=-4y^2+12y-9\)
7) \(-\left(5x+2y\right)^2=-25x^2-20xy-4y^2\)
8) \(-\left(2x-\dfrac{3}{2}\right)^2=-4x^2+6x-\dfrac{9}{4}\)
a)
\(x-5=-1\)
\(x=-1+5\)
\(x=4\)
b)
\(x+30=4\)
\(x=4-30\)
\(x=-26\)
c)
\(x-(-24)=3\)
\(x+24=3\)
\(x=3-24\)
\(x=-21\)
d)
\(22-(-x)=12\)
\(22+x=12\)
\(x=12-22\)
\(x=-10\)
e)
\(( x + 5 ) + ( x - 9 ) = x + 2\)
\(x+5+x-9=x+2\)
\(x+x-x=2+9-5\)
\(x=6\)
f)
\(( 27 - x ) + ( 15 + x ) = x - 24\)
\(27-x+15+x=x-24\)
\(-x+x-x=-24-15-27\)
\(-x=-66\)
\(x=66\)
x - 5 = -1 x - (-24) = 3
x = -1 + 5 x + 24 = 3
x = 4 x = 3 - 24
x + 30 = 4 x = - 21
x = 4 - 30 22 - ( -x) = 12
x = - 26 22 + x = 12
x + 5 + ( x - 9) = x + 2 x = 12 - 22
x + 5 + x - 9 = x + 2 x = -10
2x - x = 2 - 5 + 9 ( 27 - x) + ( 15 + x) = x - 24
x = - 3 + 9 27 - x + 15 + x = x - 24
x = 6 27 + 15 = x - 24
x - 24 = 42
x = 42 + 24
x = 66
2/3 + 3/4=17/12
9/4 + 3/5=57/20
5/24 + 1/4=11/24
3/15 - 5/35=2/35 18/27 - 2/6=1/3 37/12 - 3=1/12
11/9 x 3/22=1/6 7/13 x 13/7=1 4 x6/7=24/7
2/5 : 3/10=4/3 3/8 : 9/4=1/6 8/21 : 4/7=2/3
\(\frac{2}{3}.x=\frac{1}{3}\)1) x-\(\frac{10}{3}\)=\(\frac{7}{15}.\frac{3}{5}\)
x-10/3=7/25
x=7/25+10/3
x=\(\frac{271}{75}\)
2)\(\frac{8}{23}.\frac{46}{24}.x=\frac{1}{3}\)
2/3.x=1/3
x=1/3:2/3
x=1/2
1)(1+x)+(2+x)+(3+x)+.....+(22+x)=77
=>1+x+2+x+.....+22+x=77
=>22.x+(1+2+3+.....+21+22)=77
=>22.x+253=77
=>22x=77-253
=>22x=-176
=>x=-8
\(\frac{2}{3}x+\frac{1}{4}x=-\frac{22}{27}\)
\(x\times\left(\frac{2}{3}+\frac{1}{4}\right)=-\frac{22}{27}\)
\(x\times\left(\frac{8}{12}+\frac{3}{12}\right)=-\frac{22}{27}\)
\(x\times\frac{11}{12}=-\frac{22}{27}\)
\(x=-\frac{22}{27}:\frac{11}{12}\)
\(x=-\frac{22}{27}\times\frac{12}{11}\)
\(x=-\frac{264}{297}\)
\(x=-\frac{8}{9}\)
Vậy \(x=-\frac{8}{9}\)
_HT_